The practice of implementation of labour market policy in Poland vs. public governance - Frączek, Maciej (Journal of Public Governance, 2015)
In the paper, an attempt is made to determine whether and to what extent the labour market policy in Poland is based on the principles of the public governance model. The author describes key attributes of public governance, essential for the specificity of labour market policy. The main subject of the paper is to place the discussion of labour market policy theory and practice in the context of the three basic attributes of the public governance model identified by Jessop (2007): ref lexive self-organization, horizontal network, and negotiated consent. The author then analyzes labour market policy in Poland, focussing on those of its mechanisms and tools used on the national, regional, and local level which are in line with the principles of public governance. Finally, labour market policy in Poland is mapped in reference to model characteristics postulated in public governance. The initial analysis shows that the labour policy currently existing in Poland is not a uniform, model construct that could be described based solely on public governance principles. Many characteristics of the model can be seen on the level of institutional solutions, but in practice, a bureaucracy model or a market model prevail. Activities undertaken as part of local and regional labour market policies show a promise of a change in this situation.